Inside polyMOFs: layered structures in polymer-based metal–organic frameworks - Bentz, Kyle C. (Chem Sci, 2020)
In this report, we explore the internal structural features of polyMOFs consisting of equal mass ratios of metal-coordinating poly(benzenedicarboxylic acid) blocks and non-coordinating poly(ethylene glycol) (PEG) blocks. The studies reveal alternating lamellae of metal-rich, crystalline regions and metal-deficient non-crystalline polymer, which span the length of hundreds of nanometers. Polymers consisting of random PEG blocks, PEG end-blocks, or non-coordinating poly(cyclooctadiene) (COD) show similar alternation of metal-rich and metal-deficient regions, indicating a universal self-assembly mechanism. A variety of techniques were employed to interrogate the internal structure of the polyMOFs, including transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and small-angle synchrotron X-ray scattering (SAXS). Independent of the copolymer architecture or composition, the internal structure of the polyMOF crystals showed similar lamellar self-assembly at single-nanometer length scales.